Due Diligence to Prevent Foreseeable Harm: The International Human Rights Agenda on Civilian Gun Violence - Barbara A. Frey (Washington University Journal of Law & Policy, 2019)
This article explains how firearms regulation became part of the United Nations’s human rights agenda. In 2002, the author of this article was appointed by a U.N. sub-commission to prepare a comprehensive study on the prevention of human rights violations committed with small arms and light weapons. The resulting report, which this article revisits, explained each U.N. member state’s responsibility to prevent its private individuals from using guns to violate others’ human rights. The article further discusses how the U.N. has developed an increased focus on the human rights aspects of gun violence in the decade since the author’s report was published.
Keywords: firearms regulation; gun violence; human rights; international human rights; foreseeable harm; United Nations